Analisis Kebutuhan UI/UX Mahasiswa Kalbis Institute Pada Studi Kasus Learning Management System (LMS) Leaps Kalbis Institute - Muhammad Kelvin Darmawan; Mira Ziveria (UNIVERSITAS KALBIS, 2023)
In this study, researchers discuss the problems faced by Kalbis Institute students when they are using the learning management system (LMS). This study aims to help solve problems with interface design solutions. The researcher used the user centered design (UCD) method as a research method, python and power BI as a data processing tool, the Slovin formula as a determinant of the sample space, and a user experience questionnaire as a testing tool.